1961
DOI: 10.1029/jz066i010p03574
|View full text |Cite
|
Sign up to set email alerts
|

The Bruderheim meteorite

Abstract: Bruderheim, a detonating bolide, fell at 1:06 a.m., MST, on March 4, 1960. The fireball traveled on an azimuth of N 100°, at a slope of 40°, with an initial atmospheric velocity of 8 to 10 miles per second. More than 300 kilograms have been recovered from the fall area, a well‐defined ellipse centered about latitude 53°54′N, longitude 112°53′W. This ellipse is 312 miles long and 214 miles wide (5.6 by 3.6 km), with its long axis N80W and the larger individuals located near its southeast apex.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

1967
1967
1991
1991

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(12 citation statements)
references
References 13 publications
2
10
0
Order By: Relevance
“…Our estimate of the proportion of feldspar in Bruderheim is very close to that of Baadsgaard et al (1961) and to the value for L-type chondrites reported by Mason (1965 Ebihara and Honda (1983), however. Such high proportions would raise the average et al (1961).…”
Section: Results Of Modellingsupporting
confidence: 81%
See 3 more Smart Citations
“…Our estimate of the proportion of feldspar in Bruderheim is very close to that of Baadsgaard et al (1961) and to the value for L-type chondrites reported by Mason (1965 Ebihara and Honda (1983), however. Such high proportions would raise the average et al (1961).…”
Section: Results Of Modellingsupporting
confidence: 81%
“…The composititons of the refined end-member phases are given in Table 4. ordinary chondrites, and Baadsgaard et al (1961) reported a very similar normative composition for Bruderheim, specifically. Based on those works and general considerations of traceelement distribution coefficients, we concluded that the elements we had determined (Na, Sc, Cr, Fe, Co, Ni, Se, La, Sm, Ebihara, 1982).…”
Section: Ol+opxmentioning
confidence: 78%
See 2 more Smart Citations
“…Much of the plagioclase is probably present both as submicroscopically fine aggregates in the interstices between large grains of opaque minerals and other silicate phase, and as microcrystalline aggregates with fine-grained pyroxene between phenocrysts of olivine and orthopyroxene, especially in several chondrules. Such discrepancy of estimation of feldspar content between norm calculation and modal analysis is also observed in the Bruderheim chondrite (Duke et al, 1961;Baadsgaad et al, 1961).…”
Section: Discussionmentioning
confidence: 81%